Does Policy on Plastic Waste Support Higher Waste Management Hierarchy Options? - Kunle Ibukun Olatayo; Paul T. Mativenga; Annlizé L. Marnewick (Recycling, 2022)
There is an urgent and growing need to further advance the plastic waste management system globally and in South Africa, due to the increasing impact of plastic waste. This study focused on the adequacy of plastic policies to sustainably manage plastic waste. Policies need to address the plastic material supply systems and the options up the waste hierarchy for them to be effective and support material circularity. The study used qualitative content analysis to assess how the evolution of plastic policies for plastic waste management in South Africa aligned with national plastic material flows and promoted options higher up the waste hierarchy. This was benchmarked with Norway and Germany, which have some of the highest plastic recycling rates. The results showed that the evolution of existing plastic policies for South Africa addresses stages of production, trade and consumption, and recycling. There is no focus on waste generation, collection and sorting. None aligned with the waste hierarchy options of rethink, reduce, reuse, repair, refurbish, remanufacture and repurpose. This policy gap supports the need for broader national plastic policy frameworks that embed a policy drive in the value chain points and promote the priority higher value measures of the waste hierarchy.